Effect of seed germinability and vigoure on seedling field emergence, seed cotton yield and some related traits of commercial cotton (Gossypium hirsutum) cultivars - آیدین حمیدی; نادره کاری هفت چشمه (علوم و فناوری بذر ایران, 2013)
In order to evaluate the effect of seed viability (germinability) on seedling field, seed cotton yielde and some related traits of commercial cotton cultivars, an experiment was conducted in 2008 and 2009 at Seed and Plant Certification and Registration seed analysis laboratory and research field at Karaj. Seeds of Mehr, Varamin, Sahel and Bakhtegancotton cultivars produced in 2007 and 2008 with 70, 80 and 90 percent germinability tested by standard germination test in laboratory. Seeds planted in field as two factor factorial experiment by 12 treatments(4 cultivarandtimes;3 seed viability) based on complete randomized block design by four replicates. Then 19 traits including primary field emergence(PFE), final field emergence(FFE), field emergence rate(FER), cumulative emergence rate(CER), mean emergence time(MET), field emergence index(FEI), seedling primary height(SH1), seedling height in second sampling(SH2),seedling height in third sampling(SH3), seedling final height(SH4), primary seedling field vigour index(PSVIF) and final seedling field vigour index(FSVIF), vegetative and reproductive branches number, final plant height, boll number and seedcotton yield per hectare determined. The results indicatedthat over standard viability seeds had high field emergence index(FEI), seedling emergence rate(SER) and primary and final field emergence(FFE) and seedling height andprimary and final seedling vigoure index in field and therefore had better field emergence and establishment. Also seeds have over standard viability had lower plant final height and vegetative branches which stated those lower vegetative growth and had more reproductive branches, boll number and weight per plant and resultant seed cotton yield per hectare. Thereafter in order to reduce seed consumption rate to recommended amount generally based on this experiment results planting seeds have90 percent germination recommended.